Investigation of low-level jet characteristics based on wind profiler observations. Issue 174 (March 2018) - Shu, Z.R.; Li, Q.S.; He, Y.C.; Chan, P.W.
Abstract: Low-level jets (LLJs) have received increasing concerns over the decades due to their close connection with various branches of meteorological and engineering applications. This study aims to provide a comprehensive investigation of LLJ characteristics based on two-year wind profiler observations in Hong Kong, in which a wide variety of LLJ characteristics, including jet speed maximum, jet height and distribution of jet direction, frequency of occurrence, statistics of wind shear coefficients associated with LLJs are explored and discussed in detail. The effect of wind speed criteria for LLJ identification on the LLJ characteristics is identified. Furthermore, the connection between LLJ characteristics and seasonality, directionality, as well as jet intensity is investigated individually. For the study of directionality, two typical jet directions derived in this study (i.e. N and E-ESE) are selected for further analysis, while for the study of jet intensity, the LLJ observations are categorized into weak, moderate and strong cases depending on the jet classification method proposed by Bonner (1968). The analyzed results suggest that the variability of the LLJ characteristics has a strong dependence on the change in seasonality, directionality and jet intensity. The discussions and conclusions from this study are expected to further enhance the understanding of the LLJ characteristics, and provide valuable implications for practical applications related to wind engineering. Highlights: Low-level jets (LLJs) are investigated based on wind profiler observations in Hong Kong. A wide variety of LLJ characteristics are explored and discussed. Effect of wind speed criteria on identification of LLJs is identified. Dependences of LLJ characteristics on seasonality, directionality and jet-intensity are investigated respectively.